Annual plant reviews, Volume 16: Intercellular communication in plants - Fleming, Andrew J (Blackwell, 2012)
Many biological phenomena are controlled by intercellular signaling systems, initiated by messenger molecules. This book presents an overview of intercellular signaling systems, capitalizing on the results of contemporary molecular biology.